2002
DOI: 10.1096/fj.01-0813com
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of microscopic human cancers in mice: alterations in the angiogenic balance accompanies loss of tumor dormancy

Abstract: Some human tumor lines do not form visible tumors when inoculated into immunosuppressed mice. The fate of these human tumor lines was followed by transfecting them with green fluorescence protein before inoculating them into mice. Although the tumor lines failed to grow progressively, they formed small dormant microscopic foci maintained at constant mass by balanced proliferation and apoptosis. Transfecting the cells with either VEGF165 or activated c-Ha-ras induced loss of dormancy, which correlated with a sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
90
0
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(98 citation statements)
references
References 42 publications
5
90
0
3
Order By: Relevance
“…Furthermore, using H2373 cells stably expressing green fluorescent protein for our in vivo study, we were able to accurately assess and quantitate peritoneal tumour colonies at the completion of treatment. This strategy has been shown to be much more sensitive for detecting and assessing tumour nodules (Udagawa et al, 2002;Oh et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, using H2373 cells stably expressing green fluorescent protein for our in vivo study, we were able to accurately assess and quantitate peritoneal tumour colonies at the completion of treatment. This strategy has been shown to be much more sensitive for detecting and assessing tumour nodules (Udagawa et al, 2002;Oh et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Both models are supported by experimental evidence. The tumor dormancy might be due to specific downregulation of cell surface molecules such as uPAR (Aguirre Ghiso et al, 1999) and angiogenic signals may then be used to terminate the dormant state (Udagawa et al, 2002). MMPs apparently also participate at this step as TIMP-1 expression by the tumor cells, but not by the surrounding tissue, significantly affects the initiation and growth of the tumors (Soloway et al, 1996).…”
Section: Metastasismentioning
confidence: 99%
“…78 The high incidence of occult human cancers suggests that this angiogenic switch may, as in the RIP-TAG model, be a relatively late event that plays a significant role in the transition from microscopic foci to macroscopic tumor. 79 These data suggested that induction of angiogenesis during multistage carcinogenesis is coordinated by an 'angiogenic switch'. VEGF signaling is primarily implicated in angiogenesis and tumorigenesis in RIP1-TAG2 mice.…”
Section: The Rip1-tag2 Modelmentioning
confidence: 98%